GSK3β Inhibitor Peptide Protects Mice from LPS-induced Endotoxin Shock - Ko, Ryeojin (The Korean Association of Immunologists, 2010)
BACKGROUND: Glycogen synthase kinase 3β (GSK3β) is a ubiquitous serine/threonine kinase that is regulated by serine phosphorylation at 9. Recent studies have reported the beneficial effects of a number of the pharmacological GSK3β inhibitors in rodent models of septic shock. Since most of the GSK3β inhibitors are targeted at the ATP-binding site, which is highly conserved among diverse protein kinases, the development of novel non-ATP competitive GSK3β inhibitors is needed. METHODS: Based on the unique phosphorylation motif of GSK3β, we designed and generated a novel class of GSK3β inhibitor (GSK3i) peptides. In addition, we investigated the effects of a GSK3i peptide on lipopolysaccharide (LPS)-stimulated cytokine production and septic shock. Mice were intraperitoneally injected with GSK3i peptide and monitored over a 7-day period for survival. RESULTS: We first demonstrate its effects on LPS-stimulated pro-inflammatory cytokine production including interleukin (IL)-6 and IL-12p40. LPS-induced IL-6 and IL-12p40 production in macrophages was suppressed when macrophages were treated with the GSKi peptide. Administration of the GSK3i peptide potently suppressed LPS-mediated endotoxin shock. CONCLUSION: Collectively, we present a rational strategy for the development of a therapeutic GSK3i peptide. This peptide may serve as a novel template for the design of non-ATP competitive GSK3 inhibitors.